Ordnance transportation - Kostadinović, Dragan S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The paper describes the restrictions on the joint transportation of dangerous goods in the same vehicle, with a focus on dangerous goods of Class 1 (explosive materials and objects with explosive materials), which are, considering their purpose, typical of the Serbian Army. It also describes the conditions under which the transport of dangerous goods does not apply specific requirements that must be met during the transport of dangerous goods, as well as a way of labellng vehicles for ordnance transportation. Introduction Dangerous Goods transport contains  materials, objects , or waste that are classified as dangerous goods in accordence with  the conditions set forth in the regulations. Due the existence of the risk of accidents in the process of executing the transport of dangerous goods, and in order to secure the execution of transport for The Serbian Army (SA), besides knowing the Directive provisions, it is necessary to know the appropriate provisions defined by ADR regulations. Group of Danger Class 1 of dangerous goods Class 1 dangerous goods include explosives, explosive substances and articles containing one or more explosive substances, except those that are too dangerous to transport or those where the dominant risk corresponds to the second class (GŠVS Sektor za logistiku TU, 2002). Depending on the design, explosion characteristics (expected risk) and packaging type, all kinds of ordnance can be divided into risk groups  as shown in Table 1 Each danger group denotes the dominant character of the present danger in accident situations. In addition to these groups given in the Instructions for Ordnance Storage, the ADR regulations define the sixth group of hazards related to the extremely insensitive articles which do not have a mass explosion hazard. Joint transport of dangerous goods Transport of dangerous goods is a specific area that requires the application of certain procedures in order to conduct safe transport and to prevent possible accidental situations and conditions hazardous to humans and the environment (Gaćeša, 2012, p.313). During handling and transport of dangerous goods, if people are not trained properly, devastating effects on people, technology and the environment can occur. Risk is further increased because certain dangerous substances can react violently when they come into contact with each other. The highest level of security during transport and storage can be provided if each item or ordnance type is stored separately. However, such an ideal transport and storage in general is not feasible. For these reasons, the regulations on the transport of dangerous goods include the prohibition of mixed cargo. Limitations for mixed cargoes are determined according to the placards on the packaging and in accordance with the ADR regulations (Table 2). From Table 2 it can be seen that ordnance (except those with classification code 1.4S) and explosive substances, as well as shock-sensitive materials, must not be transported with any other material. Transport of mixed cargoes of Class 1 Due to their specific properties, mixed cargoes of Class 1 dangerous goods may be transported in the same vehicle only if the conditions defined in terms of compatibility-affinity group (Table 5)are met. The conditions stipulated by the ADR regulations are shown in Table 3. Transporting ordnance for the Serbian Army Ordnance must not be transported and stored with items from other classes of dangerous goods presenting a hazard to ordnance (eg, flammable or combustible substances, acids, substances that cause corrosion, etc.). Different ordnance types can be shipped together in one vehicle, or stored in the same warehouse only if their compatibility is provided, i.e. if their properties and sensitivity are compatible (Table 5), so that, as such, they can be stored together without significantly increasing possibilities for accidents (GŠVS Sektor za logistiku TU, 2002). Ordnance types are classified in appropriate compatibility groups for storage if their properties and sensitivity are compatible so that, as such, they can be stored together without significantly increasing possibility of any accident, or, for a given amount, without increasing the effect of such an accident. Labels on transport vehicles for ordnance transportation When transporting ordnance, vehicles,must have transportation labels which primarily inform on the danger level during transport. Transportation labels (Figure 1) are determined by the highest risk items, if different danger groups of ordnance are transported. . The degree of risk in transport is indicated by capital Latin letters A, B or C (Table 6). Classification (VAT ID) tags, contain a class of dangerous goods, risk group, and each material group compatibility (Table 6),. It consists of numbers and letters as follows (GŠVS Sektor za logistiku TU, 2002): X. Y. P where: X - number of dangerous goods class (always 1); Y - number of risk group (a value from 1 to 5); P -  letter of the compatible group. Classification labels are placed on the packaging or transport means at the frontal (front) side or on the box lid as well as in the open space among other labels in other forms of packaging. In addition to these rules, the sender or the person responsible for the dangerous goods shipping,must know the maximum allowable quantity per transport unit for the goods of class 1 (Table 7). Transport under the regime of "small quantities" During the transport of dangerous goods under the regime of "small amount" all the ADR regulations intended for the transport of dangerous goods do not apply, i.e. there are exemptions from specific requirements in terms of: marking of vehicles, issuing guidelines on specific security measures, specially trained drivers, passengers, loading and unloading locations, special requirements that must be met by vehicles (when transporting some gases, ventilation is necessary). The measure unit used to determine the amount available for transportation under the regime of "small amount" depends on the type and packaging of dangerous substances (Table 8). Depending on the degree and type of risk hazardous materials, there are five transport categories (Table 9). The rules for the  "small amount" transport regime are used when a certain amount, or quantity is not exceeded. The method of calculating the amount of hazardous cargo available for mixed cargoes of different transport categories in one transport unit is given in Table 10. In the transport of hazardous materials classified into the same category of transport, transport facilities should be used only when the amount is not exceeded by a transport unit for a transport category, or the value of units of measurement used for the hazardous substance as free volume, which is given in the far right column of the table. Conclusion In order to avoid unintended consequences due to improper housing of dangerous goods in a vehicle or in stock, it is necessary to comply with certain prohibitions regarding joint transportation of certain hazardous materials and limits in the amount of certain hazardous materials that must be loaded into the vehicle (transport unit). Regarding the transport functions of different classes of dangerous goods, these regulations provide preventive measures to ensure safe transport and handling of dangerous goods.
Keywords: compatibility groups; ordnance; Transportation; Dangerous Goods